2021
DOI: 10.1186/s41479-021-00092-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome in COVID-19: possible mechanisms and therapeutic management

Abstract: COVID-19 pandemic is a serious concern in the new era. Acute respiratory distress syndrome (ARDS), and lung failure are the main lung diseases in COVID-19 patients. Even though COVID-19 vaccinations are available now, there is still an urgent need to find potential treatments to ease the effects of COVID-19 on already sick patients. Multiple experimental drugs have been approved by the FDA with unknown efficacy and possible adverse effects. Probably the increasing number of studies worldwide examining the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 114 publications
1
100
0
Order By: Relevance
“…Therefore, controlling the development of ARDS may also be a feasible treatment strategy for COVID-19. At present, a number of clinical studies (NCT04244591/NCT04327401/NCT04476992/NCT04306393…) are using strategies such as glucocorticoids, small molecule drugs, recombinant interferon and NO inhalation to explore the effectiveness of intervening in ARDS to affect COVID-19 ( 266 , 267 ). Perhaps this strategy will provide more evidence for the safety and efficacy of treating COVID-19.…”
Section: Potential Therapeutic Strategies and Promising Anti-sars-cov...mentioning
confidence: 99%
“…Therefore, controlling the development of ARDS may also be a feasible treatment strategy for COVID-19. At present, a number of clinical studies (NCT04244591/NCT04327401/NCT04476992/NCT04306393…) are using strategies such as glucocorticoids, small molecule drugs, recombinant interferon and NO inhalation to explore the effectiveness of intervening in ARDS to affect COVID-19 ( 266 , 267 ). Perhaps this strategy will provide more evidence for the safety and efficacy of treating COVID-19.…”
Section: Potential Therapeutic Strategies and Promising Anti-sars-cov...mentioning
confidence: 99%
“…Before COVID-19, ARDS affected 200 000 individuals annually in the USA, with a mortality rate of approximately 40% [ 2 ]. The incidence of ARDS increased substantially with COVID-19, with 30% of COVID patients admitted to hospital having ARDS of which 75% were admitted to the intensive care unit [ 3 ]. ARDS mortality is strongly associated with ventilator-induced lung injury (VILI), potentially due to the interactions between micro- and macroscale elements of the lung [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the mutations, the persistent infection in the population has been unprecedented; the lack of vaccination is another cause ( 2 ), such that massive death tolls have been reported on a real-time basis by the World Health Organization ( ). Some COVID-19 cases are accompanied by mortiferous symptoms, including acute respiratory distress ( 3 ). It has been observed that infection in patients with cancer with SARS-CoV-2 is more severe than in healthy patients ( 4 ).…”
Section: Introductionmentioning
confidence: 99%